The effect of intraoperative intermittent pneumatic compression on deep venous thrombosis prophylaxis in patients undergoing elective craniotomy - Qi, Xiang; Wang, Mengrui; Feng, Kang; Ma, Yu; Zhang, Dan; Guo, Yidi; Fan, Yujie; Jiao, Yubing; Zhang, Xiaoyu; Wang, Baoguo; Shi, Zhonghua; Sun, Yongxing (Frontiers in Neurology, 2024)
Objective Postoperative deep venous thrombosis (DVT) is commonly observed in patients undergoing craniotomy and is associated with a high incidence of pulmonary embolism and poor clinical outcomes. Herein, we investigated the prophylactic effect of DVT of intraoperative intermittent pneumatic compression (IPC) in patients undergoing craniotomy. Methods A total of 516 patients who underwent elective craniotomy between December 2021 and December 2022 were enrolled in this study. Patients were randomly assigned to the intervention group (received intraoperative IPC) or control group (without IPC). Lower extremity ultrasound was performed on both legs before and after surgery (1 h, 24 h, and 7 days post-intervention). DVT was defined as the visualization of a thrombus within the vein lumen of the leg. Coagulation and platelet function were measured at the start and end of the craniotomy. Results A total of 504 patients (251 in the intervention group and 253 in the control group) completed the study. Among these patients, 20.4% (103/504) developed postoperative DVT within the first week after surgery, with 16.7% occurring within 24 h. The incidence of postoperative DVT in the intervention group (9.6%, 24/251) was significantly lower than that in the control group (22.9%, 58/253, p < 0.001). Intraoperative IPC reduced the risk of DVT by 64.6% (0.354, 95% CI, 0.223–0.564, p < 0.001). There was no significant difference in coagulation and platelet function between the two groups (all p > 0.05). Conclusion DVT may develop within 24 h after the craniotomy. Intraoperative application of IPC reduces the incidence of postoperative DVT.